Efficient Fire Pixel Segmentation Using Color Models in Still Images - vadivu, M.Senthil; Vijayalakshmi, M.N (International Journal of Computer Sciences and Engineering, 2018)
Forest Fire causes more disasters to the environment. Detecting the fire in the early stage will play a crucial role to prevent the risky effects. The vision-based approaches have gained more impact than the conventional fire detection methods with respect to accuracy and less false alarms. A reliable and efficient computer vision based technique to retrieve fire-colored pixels in still images is proposed in this article. It adopts both RGB and L*a*b* space for segmenting the fire-colored pixels on colour feature. The proposed results are compared with the current methods. The results of proposed method bring satisfactory results than the existing techniques.